Influencing of Cultural Factors in Women Maternal Health Care: A Case Study in Tehsil Jampur, District Rajanpur of Punjab, Pakistan - Altaf, Ghani (unpublished, 2024)
Reproductive health significantly influences the overall health of individuals and society. It has been the subject of increased attention from a health viewpoint. In 2014, World Bank also emphasized the reproductive health issue by revealing that globally, 287,000 women die from complications in pregnancy and childbirth each year. This is still one of the leading causes of death and disability among women of reproductive age in low-income countries including South Asian developing countries. Pakistan is in the South Asian region with poor health indicators coupled with high poverty and illiteracy. In Pakistan on average eighty women die every day because of pregnancy-related complications. Pakistan holds the fifth position throughout the world in accordance with population. The maternal mortality ratio in Pakistan is 186 deaths per 100,000 live births. The ratio is nearly 26% higher in rural areas as compared to urban areas. (Pakistan Maternal Mortality Survey, 2019). Design of study is qualitative to use the appropriate methods and document the maternal health services, common traditional/ Indigenous practices relating to pregnancy, childbirth, and the postpartum period. The study also explores the gender and prevailing decision-making beliefs in Pakistani rural cultures. Purposive sampling used to collect data from forty-two respondents through In-depth interview and in five group discussions. Sample was the married women from age group 15-49 and have at least one child. Twenty key informant / cultural consultant (Health Professional, Health Worker, TBAs, and experienced community men and women) were interviewed for data support in Tehsil Jampur District Rajanpur. Thematically the study was analyzed on the bases of structural-agency theory and delays Modal. Study observed the maternal health services, cultural beliefs such as food habits, gender norms, religious and behavioral taboos and herbal and traditional healthcare practices in all three stages of maternity, prenatal, natal and postnatal. The study also discovers the systemic structural delays in care-seeking, household hierarchical system which marginalized the women in decision making. Male supremacy and dominancy effect the women decision-making power in healthcare-seeking and clinical intervention. Duality in faith was observed where both traditional /herbal remedies along with allopathic medicine were used simultaneously. Facility-based challenges were present in the health institutions and faced by participants including lack of equipment’s, medicine and professionalism. Financial constraints and poor road infrastructure make it a gloomier. In the light of these finding, there is a need to adopt the gender mainstreaming policy and empower women culturally at household and community level. There is also a dire to involve and strengthen the role of man in women healthcare program.